Performance profile of an updated safety measure rapid assay for bacteria in platelets. Issue 11 (3rd August 2020) - Vallejo, Remo P.; Shinefeld, Lisa; LaVerda, David; Best, Nancy; Lawrence, Gregory; Lousararian, Adam; Hornbaker, Nancy; Rasmusson, Patricia; Mintz, Paul D
Abstract: Background: The Verax PGD rapid test for bacteria in platelets (PLTs) has been updated to simplify workflow and improve specificity and sensitivity by employing a novel sequential format. The performance of this updated version, called PGD prime, was evaluated to determine its suitability for use as an FDA‐cleared "safety measure" to supplant the current PGD test. Study design and methods: Three consecutive cGMP‐manufactured lots of PGD prime were evaluated for specificity (at three separate sites), sensitivity, reproducibility, interfering substances, assay robustness, and detection in analytical growth and ultralow‐inoculum growth studies. PGD prime 's performance was compared to that of PGD. Results: Specificity studies yielded no false‐positive results among 3802 individual indate PLTs of seven different types (observed specificity, 100%). PGD prime detected all 10 PGD claim bacteria at the same limit of detection or better. Wild‐type Gram‐negative bacteria growing in PLTs were detected at earlier elapsed times than PGD by 12 to 30 hours. In growth studies, PGD prime detected bacteria growing in PLTs within the same 12‐hour interval as PGD or 12 to 48 hours earlier. Assay reproducibility was not affected by operator, day of test, or manufacturing lot. PGD prime tolerated a wide variation in volume transfers, timing, temperature, and relative humidity and was not affected by 15 of 16 potential interferents found in samples at extremely high or low levels. Conclusion: The PGD test has been successfully updated to PGD prime with an innovative sequential assay format to deliver a robust simplified workflow and improved specificity and sensitivity.